Losmapimod Protected Epileptic Rats From Hippocampal Neuron Damage Through Inhibition of the MAPK Pathway - Li, Min; Cui, Lexiang; Feng, Xuemin; Wang, Chao; Zhang, Yinmeng; Wang, Lijie; Ding, Ying; Zhao, Teng (Frontiers in Pharmacology, 2019)
Objective: This research aimed to validate the therapeutic effect and explore the underlying mechanism in losmapimod-treated epilepsy. Methods: Rat model of epilepsy was constructed with the induction of pilocarpine. Microarray analysis was performed to screen the aberrantly expressed mRNAs and the activated signaling pathways between epileptic rats and the normal control. TUNEL assay was used to indicate cell apoptosis. Hippocampal cytoarchitecture was visualized with Nissl staining. The secretion of inflammatory factors were detected by western blot, as well as the marker proteins in MAPK pathway. The Morris water maze navigation test evaluated rats’ cognitive function. Results：Activation of MAPK signaling pathway was observed in epilepsy rats. Losmapimod improved the cell viability of pilocarpine-induced neuron cells. Down-regulating MAPK phosphorylation level protected epilepsy by inhibiting hippocampal neuron apoptosis and enhancing hippocampal neuron cell viability. Losmapimod effectively improved the memory ability, reduced the frequency of the seizures, protected the neuron damage and restrained the apoptosis of neurons in epilepsy rats. Conclusion: The application of losmapimod could reverse the development of epilepsy via MAPK pathway, and could serve as a novel treatment in epilepsy with a specific molecule target.